Prevalence and Associated Risk Factor of Intestinal Parasitic Infection Between Marginalized and Non- marginalized People In AL-Turbah City. Taiz Governorate, Yemen. (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: marginalized people; parasites; al -turbah city; yemen